1976
DOI: 10.1177/039219217602409502
|View full text |Cite
|
Sign up to set email alerts
|

Science, Technology and Values

Abstract: Science may be designated as the search for the understanding of phenomena apprehended by one or more of the senses in terms of theoretically postulated entities and the interrelationships between them in such a manner that the apprehended phenomena may be deducible from them along with others for which it was not postulated and with respect to which its truth and falsity, or rather fecundity or sterility, could be judged. This continuous interplay between the theoretically postulated and the sensuously appreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the chemical engineering literature, film theory has been used to model cross-phase diffusion. This theory represents that the components of oil and gas diffusion fluxes cross the interface to reach the chemical equilibrium. , This concept has also been used in petroleum engineering to model the molecular diffusion in gas injection processes. ,,, Thus, in this article, film theory has been used to simulate molecular diffusion across two phases and shown that this theory is a practical approach for modeling the double cross-phase diffusion mechanism introduced in this work. A schematic of molecular diffusion fluxes is shown in Figure , which indicates that the molecular diffusion flux of components directly relates to the chemical potential gradient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the chemical engineering literature, film theory has been used to model cross-phase diffusion. This theory represents that the components of oil and gas diffusion fluxes cross the interface to reach the chemical equilibrium. , This concept has also been used in petroleum engineering to model the molecular diffusion in gas injection processes. ,,, Thus, in this article, film theory has been used to simulate molecular diffusion across two phases and shown that this theory is a practical approach for modeling the double cross-phase diffusion mechanism introduced in this work. A schematic of molecular diffusion fluxes is shown in Figure , which indicates that the molecular diffusion flux of components directly relates to the chemical potential gradient.…”
Section: Methodsmentioning
confidence: 99%
“…This theory represents that the components of oil and gas diffusion fluxes cross the interface to reach the chemical equilibrium. 20 , 21 This concept has also been used in petroleum engineering to model the molecular diffusion in gas injection processes. 14 , 18 , 22 , 23 Thus, in this article, film theory has been used to simulate molecular diffusion across two phases and shown that this theory is a practical approach for modeling the double cross-phase diffusion mechanism introduced in this work.…”
Section: Methodsmentioning
confidence: 99%